The role of seminal plasma in the regulation of inflammation and inflammatory pathways in the cervix: potential for cervical cancer progression and HIV transmission in South African women - Adefuye, Anthonio Oladele (Department of Clinical Laboratory Sciences, 2015)
Includes bibliographical references.